FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PETANI DALAM BUDIDAYA TANAMAN SEHAT KOMODITAS PADI (Oryza sativa L.) DI KALURAHAN TIRTOMARTANI KAPANEWON KALASAN KABUPATEN SLEMAN (Influencing Farmers Interest in Healthy Rice (Oryza sativa L.) Cultivation in Tirtomartani Village Kalasan Subdistrict Sleman Regency) - Afmelia, Putri; Sukadi, Sukadi; Sadiyah, Fitria Naimatu (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2025)
This study aims to analyze the factors that influence farmers’ interest in adopting healthy cultivation (BTS) of rice (Oryza sativa L.) in Tirtomartani Village, Kalasan Subdistrict, Sleman Regency. A quantitative approach was used, involving 64 farmer respondents who had adopted healthy cultivation practices. Data were analyzed using multiple linear regression to examine the effect of non-formal education, agricultural extension support, government support, and market access on farmers’ interest. The results showed that only two variables had a significant effect: non-formal education and government support. This indicates that increased participation in training and extension activities, as well as strong government involvement through supportive policies and infrastructure, play a critical role in encouraging farmers to adopt healthy and sustainable rice farming practices. These findings are expected to serve as a reference for agricultural extension agents, policymakers, and related stakeholders in designing effective empowerment programs.Keywords: Interest, Healthy Cultivation, Rice, Non-Formal Education, Government Support.